(3cJGH aj BdGJ GdSGYGJ GdJi JSei QNGeGJs - (3KGHJ Hf bQI Hf RgQhf GdMQGfj GdUCHrj, CHh GdMSf,J (B288 (3g` s
(3ChdgG (B:s
(3Ef GdBJ GdSGYGJ GdJi JQSe NWhW SGYGJgG ai SWM eG eYdhe Ci SWM cGf s
(3BNQgG (B:s
(3hGLYd eG Hbi LjHkG hCVQHg ai GKfi YTQ hCbSe eG GLJeY Ydi eG cfJ MaXJ aeG NQL agh CUGHY GdXd s
(3ai BNQgG HYV GdLOGhd hGdQShe efShN ef OSJhQ KGHJ Hf bQI efg (B77-(3g` hebGHd Ydjg QUMs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B98 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B101s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B385 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B5 s
Keywords: (3Gdadcs